DOI: 10.18174/413524
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of whole-genome sequence data in animal and plant breeding

Abstract: Chapter 1 General introduction Chapter 2 Whole-genome sequencing of 234 bulls facilitates mapping of monogenic and complex traits in cattle Chapter 3 1. GENERAL INTRODUCTION

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 173 publications
(337 reference statements)
0
1
0
Order By: Relevance
“…Even though the panel density of PBs is lower than CBs (50K versus 61K), PBs imputation accuracies are higher, which is likely due to the larger genetic relationships between the 60 reference sequenced pigs and the female PBs in the validation, as both population are Duroc and results in sharing more and longer haplotypes between the two populations ( Hickey et al, 2011 ), while the CB population include the three-way cross between Duroc boars and Landrace-Yorkshire sows, and therefore, there is lower genetic relationship between the 60 Duroc boars and the CB population. Several studies have investigated the imputation of low MAF SNPs when imputing to the WGS in different species such as dairy cattle ( van Binsbergen., 2017 ), beef cattle ( Froberg Brøndum et al, 2014 ), pigs ( Yan et al, 2017 ; Bouwman et al, 2018 ; Ros-Freixedes et al, 2019 ), sheep ( Bolormaa et al, 2019 ), and found a poor imputation accuracy for low MAF SNPs. For example, Ros-Freixedes et al (2019) reported imputation accuracy of 0.79 for MAF between 0.005 and 0.028 ( n = 2,111), and 0.93 for MAF above 0.028 ( n = 25,968) with simulated data, and for accuracy ranging from 0.51 ( n = 11,312) for MAF <0.001 to 0.93 ( n = 89,701) for MAF ≥0.028 in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the panel density of PBs is lower than CBs (50K versus 61K), PBs imputation accuracies are higher, which is likely due to the larger genetic relationships between the 60 reference sequenced pigs and the female PBs in the validation, as both population are Duroc and results in sharing more and longer haplotypes between the two populations ( Hickey et al, 2011 ), while the CB population include the three-way cross between Duroc boars and Landrace-Yorkshire sows, and therefore, there is lower genetic relationship between the 60 Duroc boars and the CB population. Several studies have investigated the imputation of low MAF SNPs when imputing to the WGS in different species such as dairy cattle ( van Binsbergen., 2017 ), beef cattle ( Froberg Brøndum et al, 2014 ), pigs ( Yan et al, 2017 ; Bouwman et al, 2018 ; Ros-Freixedes et al, 2019 ), sheep ( Bolormaa et al, 2019 ), and found a poor imputation accuracy for low MAF SNPs. For example, Ros-Freixedes et al (2019) reported imputation accuracy of 0.79 for MAF between 0.005 and 0.028 ( n = 2,111), and 0.93 for MAF above 0.028 ( n = 25,968) with simulated data, and for accuracy ranging from 0.51 ( n = 11,312) for MAF <0.001 to 0.93 ( n = 89,701) for MAF ≥0.028 in pigs.…”
Section: Discussionmentioning
confidence: 99%